EFFECTIVENESS OF COMPENSATION MANAGEMENT IN PRIVATE FINANCIAL ENTERPRISES - Aneesh S. (MIRROR, 2018)
After the era of LPG, the role private sector has increased and they contribute a lot to the exchequer of the economy. The employment potentiality of the sector also increased but the average earnings per employee in this sector is not up to the mark. Its true in almost all the private enterprises, private sector financial enterprises is not an exception to the general phenomenon. This paper examines the compensation administration of private sector financial enterprises in Kerala.